PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN MONOPOLI TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS V PADA MATERI BANGUN RUANG DI MI MIFTAHUL HUDA - Akhmad Fauzi; Rani Arnia, Rani (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2022)
According to the results of the PISA score in 2018, Indonesia occupies 72nd place out of 79 countries in numeric literacy. One of the reasons is that learning is still monotonous. Monopoly learning media is a media game where students can play an active role during education. This study aims to determine the effect of using monopoly learning media on the mathematical reasoning abilities of fifth-grade students on the material of the spatial structure. This type of research is a quantitative one-group pretest-posttest design research. A research sample of class V, which amounted to 20 students, was given treatment. The results of the data analysis showed that the students' mathematical reasoning ability increased from the pretest score of 61.00 to 73.40 in the posttest. Then using paired sample t-test data analysis, the results obtained are 0.000 at a significance level of 0.05 (0.000 <0.05), so H0 is rejected, and Ha is accepted. So it can be concluded that there is an effect of using monopoly learning media on the mathematical reasoning ability of class V students in the material of spatial construction.